Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Acceptance of Self-Sampling Among Long-Term Cervical Screening Non-Attenders with HPV-Positive Results: Promising Opportunity for Specific Cancer Education - Sonia Andersson; Karen Belkić; Miriam Mints; Ellinor Östensson (Journal of Cancer Education, 2021)
This study aims to investigate acceptance of vaginal self-sampling for high-risk human papilloma virus (HPV) among long-term screening non-attenders at increased cervical cancer risk and to identify leverage points to promote screening adherence among these women. Forty-three long-term screening non-attenders performed home vaginal self-sampling for HPV, had positive HPV results, and subsequently attended gynecologic examination. Sixteen (37.2%) had high-grade cervical intraepithelial neoplasia (CIN2 or 3), and two had invasive cervical cancer. Forty-one of these women completed a questionnaire concerning Specific Knowledge about HPV, CIN, and cervical cancer, potential barriers to screening and views about self-sampling. Results were compared with 479 women treated for CIN2+ who attended gynecologic follow-up and also performed self-sampling. Significant multivariate predictors of long-term non-attender status compared with referents were low Specific Knowledge, high confidence in self-sampling, and potential barriers—refraining from activity to attend gynecologic examination, needing another's help to attend, and long travel time. Non-attenders citing fear/refraining from gynecologic examination as why they preferred self-sampling significantly more often had lowest Specific Knowledge compared with other non-attenders. All non-attenders could envision themselves doing self-sampling again while only 74% of referents endorsed this statement ( p = 0.0003). We conclude that HPV self-sampling is an acceptable option for women at increased cervical cancer risk who have been long-term screening non-attenders. Educational outreach to enhance Specific Knowledge about HPV, CIN and cervical cancer is critical. Those non-attenders who explicitly avoid gynecologic examinations need special attention. Trial Registry: Clinicaltrials.gov NCT02750124

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)